The phenomenon symptoms experienced of long covid-19 by students’ survivor after confirmed covid-19 - Ruhyanudin, Faqih; Afandi, Irvan; Rahayu, Henik Tri; Nur Rohmah, Anis Ika; Purwanto, Edi; Agustiyaningsih, Titik; Ubaidillah, Zaqqi; Alhusna, Chairul Huda; Sunardi, Sunardi; Herawati, Tiwuk; Syamsiah Anwar, Jamilatus (Jurnal Keperawatan, 2024)
Introduction: COVID-19 survivors often experience symptoms of recurrence or symptoms similar to those when confirmed positive. COVID-19 also has an impact on the physical, psychological, and spiritual health aspects of its survivors. This research aims to determine the health status of COVID-19 survivors after confirmation. Objectives: This research aims to determine the health status of COVID-19 survivors after confirmation. Methods: This quantitative descriptive research was conducted on 65 nursing students in Malang who were selected using the Accidental Sampling technique. Data was collected by providing an online questionnaire via Google Forms. The instruments used in this research were the post-COVID-19 Recovery Clinic Baseline Questionnaire, DASS-21, and the Spiritual Attitude and Involvement List (SAIL). The data was analyzed using Descriptive Analysis. Results: Research shows that the most common physical signs and symptoms during confirmed COVID-19 are loss of taste and smell, fever, shortness of breath, cough, and fatigue. Meanwhile, the symptoms still felt after recovery are changes in the color of the fingers, rashes, diarrhea, and hoarseness. Cough without phlegm and mucus occurred in 43.1%, and shortness of breath was experienced by 42.9% of respondents in the moderate category. Fatigue in the moderate category was felt by 58.3% of respondents. The results of psychological status showed that depression symptoms in the moderate and very severe category were 46.2%, anxiety in the very severe category was 75.4%, and stress symptoms in the very severe category were 38.5%. Regarding spiritual status, the majority are in the sufficient category, namely 68%. Conclusions: Some of the physical signs and symptoms, psychological changes, and spiritual status at the time of confirmation of COVID-19 are still felt even though they have been declared hostile to COVID-19.